Numerical solutions for partial differential equations : problem solving using mathematica /: problem solving using mathematica. (2017) - Ganzha, V. G (Victor Grigorʹevich), 1956-; Vorozhtsov, E. V (Evgenii Vasilʹevich), 1946-
No abstract available